Zero Trust Architecture as a New Paradigm in Cyber Security - Andi M. Yusuf; Dian Megah Sari; Hilda Ashari; Hamdy Nur Saidy; Musawwir (Program Studi Teknik Komputer, 2025)
The traditional perimeter-based security model has proven inadequate in addressing modern cybersecurity challenges characterized by cloud adoption, remote work, and sophisticated cyber threats. This mixed-methods study examines Zero Trust Architecture (ZTA) as an emerging paradigm that fundamentally shifts security principles from